Geothermal Use in Europe - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2001)
Geothermal energy has been used for thousands of years in Roman and Ottoman baths and district heating in France during the middle ages, and for extracting various borate compounds at Lardarello, Italy, starting in the 1700s. These uses and their impacts on the local population can be read in detail in “Stories from a Heat Earth” edited by Cataldi, Hodgson and Lund (1999) and available from the Geothermal Resources Council. More recently, extensive direct heat utilization projects have been undertaken in many central European countries, and electric power developed extensively in Italy and Iceland. Finally, geothermal heat pumps have come into their own in Austria, Switzerland, Germany and Sweden